Reactionary tensioners to combat and progressive tensioners to encourage to achieve institutionalization and public innovation in Latin America - Yusef Zehab (International Journal of Science and Society, 2022)
The purpose of this article is to present a set of theoretical and practical reflections on the current situation and proposals for the future of the processes of institutionalization and innovation of public administrations in Latin America. More specifically, the objectives of this text are two: a) to expose in an articulated way and by way of diagnosis the set of reactive tensors that have hindered, and even aborted during the last years, the processes of institutionalization and innovation of the administrations public from Latin America; b) present a set of progressive tensors, by way of proposals, that must be encouraged and incentivized in order to achieve public administrations in Latin American countries that combine greater institutional strength with a greater capacity for innovation in the definition and management of their policies. It is about advancing in the ambitious intention of combining greater institutional capacities, which provide institutional and legal security to Latin American societies, with superior potential for innovation to face the demands and requirements derived from modernity.